Pengaruh Modal, Tenaga Kerja,dan E-commerce terhadap Pendapatan UMKM di Kota Bandar Lampung (Studi Kasus Sentra Keripik Pisang Pagar Alam) - Priska Diana Santri; Neli Aida (Journal on Education, 2023)
This study aims to determine the effect of capital, labor, and e-commerce on the income of UMKM Pagar Alam Banana Chips Center. The primary data in this study were obtained by conducting interviews and giving questionnaires to MSME actors. This study uses multiple linear regression analysis to determine the effect of variables that affect income. The results of the study showed that the variables of capital and labor had a positive and significant effect on the income of the Pagar Alam Banana Chips Center UMKM. Meanwhile, the e-commerce variable has a positive and insignificant effect on the income of the Pagar Alam Banana Chips Center UMKM.